2019
DOI: 10.1016/j.ijcard.2018.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Does total volume of physical activity matter more than pattern for onset of CVD? A prospective cohort study of older British men

Abstract: Aims With increasing age, physical inactivity and sedentary behaviour levels increase, as does cardiovascular disease (CVD) incidence. We investigate how device-measured sedentary behaviour and physical activity (PA) are related to CVD onset in men aged 70+; whether the total volume of activity is more important than pattern. Methods and results Prospective population-based cohort study of men recruited from 24 UK General Practices in 1978–80. In 2010–12, 3137 survivors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(105 citation statements)
references
References 38 publications
8
96
1
Order By: Relevance
“…The study had up to 5 years of follow-up and was conducted only among older women. However, our results appear generalizable to men given a recent study 38 of 1181 older British men that reported an HR for light PA of 0.74 (95% CI, 0.41-1.34) for incident CVD events, which is remarkably similar to the HR of 0.78 (95% CI, 0.60-1.00) in the present study. Longer-term prospective studies with inclusion of both sexes are needed to increase the strength of the evidence base on light PA in relation to CVD prevention.…”
Section: Discussionsupporting
confidence: 89%
“…The study had up to 5 years of follow-up and was conducted only among older women. However, our results appear generalizable to men given a recent study 38 of 1181 older British men that reported an HR for light PA of 0.74 (95% CI, 0.41-1.34) for incident CVD events, which is remarkably similar to the HR of 0.78 (95% CI, 0.60-1.00) in the present study. Longer-term prospective studies with inclusion of both sexes are needed to increase the strength of the evidence base on light PA in relation to CVD prevention.…”
Section: Discussionsupporting
confidence: 89%
“…Consequently, there has been a request for more studies investigating the association of objectively measured PA of different intensities and sedentary behavior with clinical health outcomes [16]. In particular, the association of LPA and ST with CVD and mortality in older people has gained increased attention; however, the findings are inconsistent [23][24][25][26]. This type of research has high clinical relevance given that there may be a misconception of the volume and intensity of PA that is necessary to reduce the risk of CVD which acts as a barrier towards PA [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…sitting and lying) or in moderate-to-vigorous physical activity (MVPA), 7 of which both are important for cardiovascular health. 10,11 Third, as studies have established a strong association between ambulation status and PA after stroke, 12 it is likely that the total daily PA and within-day PA patterns differ between survivors with varying abilities to ambulate. Still, most previous studies have explored PA among stroke survivors with mild mobility impairments.…”
Section: Introductionmentioning
confidence: 99%